Alcohol‐related harm minimization practices among university students: Does the type of residence have an impact?. Issue 4 (12th June 2018) - Hepworth, Julie; Schofield, Toni; Leontini, Rose; Germov, John
Abstract : Background: The culture of 'risk‐related alcohol use' has been identified as an intrinsic part of university life for many students, especially those in residential colleges in English‐speaking countries. While the prevailing approach to managing drinking in these countries is harm minimization, little is known about students' uptake of these practices or the relationship of them to students' type of residence. Objective: To examine the ways in which type of residence may impact alcohol‐related harm minimization practices among university students. Design: A qualitative research design using focus group methodology informed all aspects of the study. Methods: University students ( N  = 70) aged 18–24 years and differentiated by their type of residence were recruited from universities in Australia. Nineteen audio‐recorded focus groups were conducted. Systematic qualitative analysis was used to identify the main themes. Results: Students reported risk‐related alcohol use and alcohol‐related harms as either consumers or having witnessed others' consumption through three main themes: (1) The pervasiveness of alcohol use and harms; (2) Perceived safety and physical spaces; and (3) Gender‐based alcohol‐related harms. Harm minimization practices were talked about in terms of four themes: (1) Policy ineffectiveness; (2) Pre‐drinking planning; (3) Friends look after friends; and (4) Help‐seeking as a covert activity. Conclusions: Alcohol use by university students occurs with limited knowledge of harm minimization policies or practices. Students do engage in ad hoc harm minimization practices usually developed during their first year at university through specific 'drinking cultures' that are constituted by various factors including their type of residence. Statement of contribution What is already known on this subject? Previous research has strongly indicated that university students' heavy alcohol consumption is linked with social and environmental factors such as marketing alcohol, low cost, availability, 'wet' environments, and shared accommodation. However, little is known about what, if any, alcohol‐related harm minimization practices students employ and if type of residence has an impact on these practices. What does this study add? This study is one of the first to examine alcohol‐related harm minimization practices among university students and type of residence demonstrating the impact of social environments on drinking and related practices. Regardless of type of residence, university students were either not aware of university and residential college alcohol policies or found them unclear. Students do engage in ad hoc harm minimization practices usually developed during their first year at university through specific 'drinking cultures' that are constituted by various factors including the type of residence. Two practical recommendations are made in this study to develop alcohol‐related harm minimization related to university students.